“Here’s what you need to know”: An analysis of clickbait narratives on chilean outlets’ Facebook News” - Miranda Bustamante, María de los Angeles (2025)
ABSTRACT: The aim of this study was to characterize clickbait discursive strategies in Facebook posts from the five most trusted news media outlets in Chile and analyze their correlations with user engagement (seminality). A quantitative discourse analysis was conducted, applying a matrix of clickbait narrative indicators to a sample of 4316 news posts. The findings revealed that 68% of posts contain clickbaits and the absence of the most relevant data was the most frequent narrative. However, only paralinguistic clickbait narratives and user-directed questions stimulated the UGC (User-Generated-Content). Conversely, those strategies that compromise informational content are associated with a decline in such engagement. In conclusion, the investigation suggests that repetition and serialization of relevant information, bullet point lists and user-addressed questions are four effective strategies to reconcile the need for journalistic companies to balance financial sustainability through clicks with their social responsibility of fostering news into a conversation.